Podcast Learning to Increase Students' Learning Motivation in University - Mumtahana, Lusia; Zahidi, Salman; Mawarda , Alfina indi (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2025)
Using podcast as a learning medium has proven effective in increasing student motivation and learning outcomes in university, especially in Islamic Education courses. Learning strategies tended to use traditional methods such as lectures, which were less interesting and reduced learning interest. However, after implementing the podcast, there is a significant increase in students' understanding, motivation, and participation. The podcast allows students to learn independently and flexibly according to their needs and supports constructivist learning theory, emphasizing tools' role in the learning process. The advantages of Podcasts include flexibility of time and place, the ability to repeat material, adaptation to auditory learning styles, and content creativity. By integrating multimedia elements such as sound and music, podcasts also fulfil the principles of multimedia theory, which increases understanding and absorption. This study used the Research and Development (R&D) method to design effective podcast learning. According to the ARCS motivation model, the results showed that podcasts were relevant to students' needs and could attract attention, build self-confidence, and provide satisfaction in the learning process. For optimal results, using podcasts requires special strategies, such as short duration, thorough materials preparation, training for lecturers, and multimedia elements integration. In addition to being a learning tool, Podcasts encourage creative collaboration between lecturers and students. With this approach, podcasts are expected to be an innovative medium that supports a more relevant, flexible, and enjoyable learning process in the digital era.